2020
DOI: 10.3390/antiox9090786
|View full text |Cite
|
Sign up to set email alerts
|

The Phosphodiesterase Type 5 Inhibitor Sildenafil Improves DNA Stability and Redox Homeostasis in Systemic Sclerosis Fibroblasts Exposed to Reactive Oxygen Species

Abstract: Systemic sclerosis (SSc) is a multi-system connective tissue disease characterized by the increased deposition of extracellular matrix proteins such as collagen and fibronectin. Although the pathogenesis is not completely understood, a number of studies suggest that free radicals could be the major contributors to the disease. Indeed, different studies demonstrated how oxidative stress could contribute to the fibrotic process activation at the level of the skin and visceral organs. Emerging evidences highlight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 63 publications
(80 reference statements)
2
27
0
Order By: Relevance
“…These compounds have recently showed antioxidant effects in different organs of animal models. This effect is achieved through the reduction of endogenous superoxide formation and the increase in the antioxidant enzymes’ activity [ 9 , 10 , 11 , 13 , 15 , 16 ]. Moreover, an improved mitochondrial integrity [ 11 , 21 ], a decreased tissue malondialdehyde and increased SOD and GPx activity levels were found following tadalafil administration [ 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These compounds have recently showed antioxidant effects in different organs of animal models. This effect is achieved through the reduction of endogenous superoxide formation and the increase in the antioxidant enzymes’ activity [ 9 , 10 , 11 , 13 , 15 , 16 ]. Moreover, an improved mitochondrial integrity [ 11 , 21 ], a decreased tissue malondialdehyde and increased SOD and GPx activity levels were found following tadalafil administration [ 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in addition to their role in the treatment of pathologies, in vitro and in vivo studies reported that PDE5Is (e.g., sildenafil, vardenafil, tadalafil) also possess antioxidant effects in different tissues/organs [ 9 , 10 , 11 , 12 , 13 , 14 ]. For instance, it has been shown that sildenafil citrate has protective effects against oxidative stress by inhibiting free radical formation and supporting antioxidant redox systems [ 13 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intracellular superoxide dismutase activity was measured using a commercial assay kit (Cayman Chemical Company, Ann Arbor, MI, USA) following the manufacturer’s instructions. Results were expressed as units/milligrams of protein tested [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…Thiobarbituric acid reactive substances. TBARS levels were assayed by spectrophotometric analysis [ 35 ]. The methodology measured malondialdehyde (MDA) and other aldehydes produced by lipid peroxidation induced by hydroxyl-free radicals.…”
Section: Methodsmentioning
confidence: 99%